2012
DOI: 10.2139/ssrn.2035833
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Returns to Task-Specific Skills and Gender Wage Gap

Abstract: How did skilled-biased technological change affect wage inequality, particularly between men and women? To answer that question this paper constructs a task-based Roy model in which workers possess a bundle of basic skills, and occupations are characterized as a bundle of basic tasks. The model is structurally estimated using the task data from the Dictionary of Occupational Titles and the PSID. The main empirical finding is that men have more motor skills than women, but the returns to motor skills have dropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 32 publications
6
51
0
1
Order By: Relevance
“…The strength of this approach is to reduce many discrete occupations into a finite‐dimensional and economically interpretable task‐space. Yamaguchi () estimated the model using correlated random effects, which express workers' unobserved time‐invariant skills as a function of all observed characteristics and their labor market history. This yields changes in task‐specific intercepts, which may be interpreted as task prices, and in slopes, which may be interpreted as relationships between skills and tasks.…”
Section: The Propensity Methods For Estimating Task Prices and Amenitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of this approach is to reduce many discrete occupations into a finite‐dimensional and economically interpretable task‐space. Yamaguchi () estimated the model using correlated random effects, which express workers' unobserved time‐invariant skills as a function of all observed characteristics and their labor market history. This yields changes in task‐specific intercepts, which may be interpreted as task prices, and in slopes, which may be interpreted as relationships between skills and tasks.…”
Section: The Propensity Methods For Estimating Task Prices and Amenitiesmentioning
confidence: 99%
“…Yamaguchi found that the returns to motor tasks have declined, hurting male compared to female workers, while returns to cognitive tasks have been unchanged.…”
mentioning
confidence: 99%
“…Auch die sehr aktuelle Problematik der Arbeitsplatzvermittlung für MigrantInnen wurde mit Hilfe des TBA zu beleuchten versucht (Haas, Lucht, und Schanne 2013). Und auch altersspezifische (Gordo und Skirbekk 2013) und geschlechtsspezifische (Yamaguchi 2013) Lohnunterschiede wurden unter dieser Perspektive zu erklären versucht.…”
Section: Einleitung -Der "Task-based Approach"unclassified
“…According to this view, occupations are bundles of tasks necessary to successfully accomplish a job. Early work using this model has associated the abovementioned narrowing of the gender wage gap to two factors: On the one hand, to the higher occurrence of female workers in cognitive‐intensive activities (Bacolod and Blum ), which have been increasingly valued by employers, especially with the diffusion of information and communication technologies (Autor, Levy, and Murnane ; Black and Spitz‐Oener ); on the other, to the displacement of male workers by technological progress, traditionally concentrated in motor‐intensive occupations (Yamaguchi ).…”
Section: Introductionmentioning
confidence: 99%
“…Our work is close to the stream of research measuring tasks at the occupational level and applying the task approach to explain the evolution of the gender gap in the United States between the 1970s and the 1990s. In this framework, Yamaguchi () measured motor and cognitive tasks from the Dictionary of Occupational Titles (DOT) and found that technological progress contributed to the narrowing of the gender wage gap by substituting male workers concentrated in motor‐task–intensive occupations. Bacolod and Blum (), instead, explored the additional contribution of changes in returns to people tasks beyond the contribution of changes in returns to cognitive and motor tasks to the wage gap.…”
Section: Introductionmentioning
confidence: 99%